ANALISIS PENANAMAN SIKAP NASIONALISME PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V A MI SALAFIYAH TUGUNG SEMPU BANYUWANGI - Devi Wahyuning Tyas; Eka Ramiati; Moh. Hayatul Ihsan (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2024)
This research aims to determine the instillation of students' nationalist attitudes in Pancasila education subjects at MI Salafiyah Tugung Sempu. This research is a type of qualitative research field research (field research) by describing and analyzing the results of cultivating nationalist attitudes in Pancasila education subjects in the VA MI Salafiyah Tugung Sempu class. The researcher carried out the data collection process using three methods, namely observation, interviews and documentation. For data analysis, descriptive analysis is used by reducing data, presenting the data, then drawing conclusions. Meanwhile, for the validity of the data, researchers used triangulation techniques. The results of the research show that the analysis of the cultivation of nationalistic attitudes in Pancasila education lessons for the VA MI Salafiyah Tugung Sempu class for the 2023/2024 academic year includes, among other things; 1) habituation; 2) exemplary; 3) providing contextual examples and learning through stories and media, such as pictures of heroes. The nationalist attitudes that exist in class VA students are as follows; 1) the disciplined attitude of class VA students is demonstrated by always obeying school regulations; 2) an attitude of willingness to sacrifice is shown by class VA students always being willing to help when a friend is in trouble, for example helping when a friend has difficulty understanding the lesson material; 3) an honest attitude is demonstrated by always doing the assignments or tests given by the teacher yourself; 4) the attitude of unity and unity possessed by class VA students is that they always respect differences of opinion expressed between themselves and other classmates; 5) VA class students have shown an attitude of love for their country, namely in the form of good use of Indonesian when learning in class, and always using locally made products such as bags, shoes and stationery.